Writing for Publication. Issue 2 (1st September 2017) - Dustin, Daniel; Wilson, Cait; Bennett, Troy; Verbos, Rose I.
Abstract: This paper recounts our collective experience in "Writing for Publication, " a one-credit graduate seminar conducted for the first time in the fall of 2015 in the Department of Parks, Recreation, and Tourism at the University of Utah. Enrollment in the course required graduate standing and first drafts of manuscripts the students hoped to refine for publication. The paper summarizes what we learned in the course about what it takes to advance an idea from concept to completion in a fashion that makes one's thinking worthy of public consideration.